2020
DOI: 10.1097/ruq.0000000000000530
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Bedside Lung Ultrasound as a Rapid Triage Tool for Suspected Covid-19 Cases

Abstract: Objectives The novel coronavirus disease 2019 (Covid-19) outbreak began in China. The characteristic of the disease is development of pneumonia. We aimed to investigate the accuracy of bedside lung ultrasound (BLUS) for diagnosing Covid-19 pneumonia, and its effectiveness for the correct triage of patients with suspected Covid-19 in the emergency department (ED). Methods This study was a prospective, cross-sectional cohort study. During their shifts, 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…Meanwhile, Bosso et al [18] found a marginally higher sensitivity (73%) and specificity (89%). By contrast, other groups [23][24][25][26][27] used alternative scoring methodologies and reported high sensitivities ranging from 90% to 100%. The specificity was a consistent trade-off in most studies [22,24,27,28].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Meanwhile, Bosso et al [18] found a marginally higher sensitivity (73%) and specificity (89%). By contrast, other groups [23][24][25][26][27] used alternative scoring methodologies and reported high sensitivities ranging from 90% to 100%. The specificity was a consistent trade-off in most studies [22,24,27,28].…”
Section: Discussionmentioning
confidence: 97%
“…The diagnostic performance discrepancy noticeable in the LUS in COVID-19 literature can be explained by the varying definitions of LUS outcome measure (i.e., how to interpret the images). Some studies have merely used any presence of B-lines or consolidations indicative of COVID-19 [21,25,27,32]. Others developed an arbitrary LUS scoring system based on a 5-point Likert scale [24] or a 6-point system [28].…”
Section: Discussionmentioning
confidence: 99%
“…During the last year, studies have shown that typical chest CT patterns of COVID-19 viral pneumonia include multifocal bilateral peripheral ground-glass areas associated with subsegmental patchy consolidations, mostly subpleural, and predominantly involving lower lung lobes and posterior segments [28][29][30][31][32]. In more detail, chest CT images of COVID-19 patients could be evaluated using the following characteristics [33][34][35][36][37][38][39][40]:…”
Section: Ct Diagnosis Algorithmsmentioning
confidence: 99%
“…A total of 1896 documents were retrieved. After reading the titles, abstracts, and full text of the documents, nine articles were included in the analysis [8][9][10][11][12][13][14][15][16] (Figure 1).…”
Section: Literature Selection Processmentioning
confidence: 99%